Sustainable Innovation: Marketing Strategies to Increase Adoption of Permeable Paving Blocks in Environmentally Conscious Markets - Kumaat, Arief P.; Supit, Vekky; Paendong, Melky K. E.; Peginusa, Stefani S. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study focuses on developing marketing strategies to increase the adoption of permeable paving blocks, an environmentally friendly product. Using a SWOT analysis, the research identifies strengths such as eco-friendly benefits and weaknesses like limited market awareness. The opportunities involve growing demand for green products, while threats include competition from traditional materials. Data were collected through surveys and interviews with industry experts. Results show that leveraging product sustainability and tapping into government incentives can boost sales, while addressing market education gaps is essential. Strategic use of social media and partnerships with eco-conscious businesses further enhances product visibility. This research provides actionable strategies to improve market positioning and product adoption.